ANALISIS WACANA KRITIS PADA TAJUK (ANTI) KORUPSI DI SURAT KABAR BERBAHASA INDONESIA - Hari Bakti MArdikantoro (LITERA, 2014)
This study aims to describe newspaper attitudes towards and views of corruptioncases in Indonesia, manifested in (anti-)corruption editorials. Newspaper attitudes aremanifested through two frames, namely the one criticizing corruption news and theother supporting corruption news. The data were collected through a literature reviewand a recording method. They were analyzed by the correspondence and participatorymethods. The findings are as follows. First, by criticizing corruption news, Koran Tempoin its two editorials indicates a disagreement over corruption news. The disagreement iscaused by several weird facts in the court and the defense for the corruption investigatorwho, quite the contrary, was sent to prison. Second, with a frame of supporting corruptionnews, Kompas, Republika, Koran Tempo, Jawa Pos, and Suara Merdeka have attitudes andviews indicating agreement to support corruption news in newspapers. The supportrefers to efforts to eradicate corruption that can be manifested in the arrest of a suspectin corruption, the court, and the verdict on a suspect in corruption.